Методи оптимізації часу лікаря в процесі заповнення полів консультаційного висновку в медичних інформаційних системах - Бабічева, А. К.; Редін, Д. В. (ХНУРЕ, 2023)
The purpose of this reserch is to study the methods of forming doctor's consulting conclusions based on the results of clinical analysis and other special studies. The main components of the advisory opinion are analyzed. The main ways of their formation are considered. Also, special attention was paid to saving the doctor's time when forming a consulting conclusions in order to increase the number of patients who can be provided with medical services.